Mental Health in an Islamic Perspective: A Conceptual Analysis of Islamic Education Psychology and Its Implications for the Development of Muslim Personality - Ma’rifah, Ma’rifah; Alimuddin, Alimuddin; Supriandi, Supriandi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Mental health is an important foundation in shaping the quality of human life because it affects mindset, emotional stability, behavioral control, and social abilities. This research aims to examine the concept of mental health in an Islamic perspective through the framework of Islamic Educational Psychology (PPI) and explore its implications for the development of Muslim personality. The research method uses a qualitative approach based on conceptual analysis and literature studies by referring to primary sources such as the Qur'an, hadith, as well as the thought of classical and contemporary scholars, as well as secondary sources from scientific articles and academic literature. The results of the study show four main points: (1) mental health in Islam is holistic and theocentric, namely spiritual, emotional, moral, and social balance centered on a relationship with Allah; (2) the Islamic personality structure of al-fitrah, al-nafs, al-qalb, and al-'aql became the foundation of mental health diagnostics; (3) Tazkiyah al-Nafs has been proven to be effective as a model of preventive, curative, and developmental psychospiritual therapy; and (4) the values of monotheism, ihsan, patience, and tawakal act as a spiritual coping mechanism that strengthens psychological resilience. These findings confirm that Islamic Educational Psychology has a comprehensive contribution to fostering mental health, especially in the educational environment, through an approach that balances intellectual, emotional, and spiritual aspects to produce civilized, resilient, and noble personalities of Muslims.